Development of Digital Twin-based Learning Videos in Early Childhood Learning Media Courses - Kurniawan, Andri; Kuswandi, Dedi; Aulia, Fikri; Badiah, Lutfi Isni (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
This research aims to develop a learning video based on Digital Twin technology for the Early Childhood Learning Media course. This learning media is designed to increase students' understanding, active involvement, and learning motivation by utilizing realistic and interactive virtual representations. This research used the Research and Development (RnD) method with the DDD-E development model (Decide, Design, Develop, Evaluate). 10 students were selected as research subjects for a pilot study. The evaluation involved multimedia experts, material experts, and students, with the average validation results showing high feasibility (above 89%). The results showed that the Digital Twin-based learning video facilitated the visualization of abstract concepts, increased enthusiasm, and facilitated students' independent learning through integration with the Learning Management System (LMS). This study recommends using this media to support more effective, innovative, and relevant education in the era of the Industrial Revolution 4.0. For future research, it is recommended to expand the scope of implementation in other courses to increase its validity and benefits.